1982
DOI: 10.2337/diacare.5.6.571
|View full text |Cite
|
Sign up to set email alerts
|

Increased Incidence of Type I Diabetes in Children of Older Mothers

Abstract: Analysis of chart data in a large series of patients with juvenile-onset, type I diabetes shows a highly significant (P less than 0.001) increased incidence in the children born to older mothers. Diabetes was also much more frequent in the late-birth-order siblings, and this appears to be an alternative expression of advanced maternal age. This observation suggests that there may be a subset of children who eventually develop type I diabetes and are at increased risk by virtue of being born to older mothers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
20
0
1

Year Published

1983
1983
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 4 publications
3
20
0
1
Order By: Relevance
“…The finding of increased risk with maternal age confirms observations from other studies [13][14][15][16][17][18] and is therefore likely to represent a real association. Social class groupings according to mothers' occupations at the time of interview, therefore post-diagnosis, were not dissimilar for cases and control subjects but there was a notable excess of case mothers unclassified because they were not in paid employment.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…The finding of increased risk with maternal age confirms observations from other studies [13][14][15][16][17][18] and is therefore likely to represent a real association. Social class groupings according to mothers' occupations at the time of interview, therefore post-diagnosis, were not dissimilar for cases and control subjects but there was a notable excess of case mothers unclassified because they were not in paid employment.…”
Section: Discussionsupporting
confidence: 81%
“…[Diabetologia (1997) 40: 933-939] childhood IDDM [12]. Other maternal factors such as maternal-child blood group incompatibility [13], older age of mothers [13][14][15][16][17], toxaemia [13], maternal diabetes [13,15] and mother's educational attainment [14,15,18] appear to influence risk. Caesarean delivery [13,15], birthweight [19,20] and birth order [15,16] have also been implicated, although the mechanisms are unclear.…”
mentioning
confidence: 99%
“…Several studies reported that older maternal age is a risk factor for T1D in the offspring [Flood et al, 1982;Wagener et al, 1983;Warram et al, 1991]. Since birth order correlates highly with maternal age, it is possible that increasing birth order is also a risk factor.…”
Section: Discussionmentioning
confidence: 99%
“…Maternal age at delivery and birth order Studies of varying design relating maternal age and birth order to type 1 diabetes were carried out between the 1960s and 1990s [64][65][66][67]. The pooled analysis of newer studies showed heterogeneity in the strength of the association, but most suggested increased risk among the offspring of mothers who were older when they gave birth [57].…”
Section: Parturitionmentioning
confidence: 99%